Establishment of Oil Palm Suspension Culture in the Sixfors Bioreactor - Rosli, Samsul Kamal (2006)
In vitro propagation is an important part of the oil palm industry’s approach towards clonal propagation of high-yielding materials. Oil palm suspension cultures have been established using the shake flask system which was developed for production of a reliable supply of regenerable plant tissues. However, this system is inefficient for fast large scale proliferation of embryogenic suspension cultures.